Cutibacterium acnes (Propionibacterium acnes) and acne vulgaris: a brief look at the latest updates. (12th June 2018) - Dréno, B.; Pécastaings, S.; Corvec, S.; Veraldi, S.; Khammari, A.; Roques, C.
Abstract: While the commensal bacterium Propionibacterium acnes ( P. acnes ) is involved in the maintenance of a healthy skin, it can also act as an opportunistic pathogen in acne vulgaris. The latest findings on P. acnes shed light on the critical role of a tight equilibrium between members of its phylotypes and within the skin microbiota in the development of this skin disease. Indeed, contrary to what was previously thought, proliferation of P. acnes is not the trigger of acne as patients with acne do not harbour more P. acnes in follicles than normal individuals. Instead, the loss of the skin microbial diversity together with the activation of the innate immunity might lead to this chronic inflammatory condition. This review provides results of the most recent biochemical and genomic investigations that led to the new taxonomic classification of P. acnes renamed Cutibacterium acnes ( C. acnes ), and to the better characterisation of its phylogenetic cluster groups. Moreover, the latest data on the role of C. acnes and its different phylotypes in acne are presented, providing an overview of the factors that could participate in the virulence and in the antimicrobial resistance of acne‐associated strains. Overall, this emerging key information offers new perspectives in the treatment of acne, with future innovative strategies focusing on C. acnes biofilms and/or on its acne‐associated phylotypes.